Health Status and Risk Assessment of Workers in Offset Printing Presses in a City of Western India - Panchani, Rhythm V; Banerjee, Anupam P; Fichadiya, Nilesh C (National Journal of Community Medicine, 2026)
Introduction: Printing press workers are exposed to occupational hazards due to the nature of their work. Awareness of these hazards is essential for prevention. This study aimed to assess health status and perceived occupational hazards among printing press workers. Methods: A cross-sectional study was conducted in thirty-five printing presses. Workers directly involved in hands-on offset printing operations with at least six months of experience were included. Health examinations were performed and work-related hazards were documented. A Risk Assessment Matrix was used to estimate risk based on likelihood and severity. Results: Among one hundred eighty-six workers examined, most were males. Common complaints included skin problems, nasal irritation, eye discomfort, burning sensation in the stomach, and calf pain. Normal body mass index and normal blood pressure were observed in a minority of workers as per JNC seven criteria. Awareness regarding chronic diseases and the harmful effects of printing dyes was low. Risk assessment indicated severe risk for finger-cut injuries and moderate risk for hand-cut injuries and electrocution. Conclusion: The study highlights health problems and perceived occupational hazards among printing press workers, though causality cannot be established. Targeted occupational health awareness and preventive programs are required to improve risk perception and promote protective practices.